2015
DOI: 10.1111/iwj.12467
|View full text |Cite
|
Sign up to set email alerts
|

Silver‐based wound dressings reduce bacterial burden and promote wound healing

Abstract: Various types of wound dressings have been designed for different purposes and functions. Controlling bacterial burden in a wound during the early phase is important for successful wound repair. Once bacterial burden is under control, the active promotion of wound healing is another important factor for efficient wound healing. This study investigated the potential of three silver-containing dressings, namely KoCarbonAg(®) , Aquacel(®) Ag and Acticoat 7, in reducing bacterial survival and promoting wound heali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(24 citation statements)
references
References 27 publications
0
23
0
1
Order By: Relevance
“…Complete reepithelialisation was observed between the 12th and 34th postoperative day (median 17⋅5 days). MRSA at DSWs was postoperatively confirmed in three patients (No 14,15,18) at the second and third dressing change. In two of these patients (No 14, 18), epithelialisation was delayed [34 days (No 14) and 26 days (No 18)].…”
Section: Group D: Patients With Mrsa At the Ulcer Sitementioning
confidence: 87%
See 1 more Smart Citation
“…Complete reepithelialisation was observed between the 12th and 34th postoperative day (median 17⋅5 days). MRSA at DSWs was postoperatively confirmed in three patients (No 14,15,18) at the second and third dressing change. In two of these patients (No 14, 18), epithelialisation was delayed [34 days (No 14) and 26 days (No 18)].…”
Section: Group D: Patients With Mrsa At the Ulcer Sitementioning
confidence: 87%
“…Effective antimicrobial wound treatment can be achieved using modern topical antiseptics, particularly polyhexanide and octenidine but also nanocrystalline silver preparations. Silver demonstrates a broad antimicrobial and anti‐fungal activity. The systemic incorporation of silver is reduced considerably by avoiding long‐term application on wound areas larger than 10% of the body surface area .…”
Section: Introductionmentioning
confidence: 99%
“…Increased levels of endotoxins produced by bacteria elevate the levels of proinflammatory cytokines, thus decreasing the production of growth factors and the deposition of collagen in wounds and delaying wound healing [25]. Then, the infection can progress from contamination to colonization and can be complicated by the presence of biofilm [26], an organized consortium of bacteria encapsulated in a self-produced extracellular polymeric substance (EPS) made of polysaccharide, protein, and DNA [27].…”
Section: Wound Infectionsmentioning
confidence: 99%
“…Lin and coworkers [60] investigated the potential of KoCarbonAg®, Aquacel Ag, and Acticoat 7 in reducing bacterial survival and promoting wound healing. In vitro results showed that the silver-containing dressings prevented bacterial (P. aeruginosa) growth in wounds by blocking the entry of external bacteria and by retaining the bacteria in the dressing.…”
Section: Wound Dressing Containingmentioning
confidence: 99%